PENDIDIKAN ISLAM SEBAGAI TERAPI BAGI TERPIDANA PENGGUNA NARKOBA YAYASAN PUSAT REHABILITASI NARKOBA AR-RAHMAN PALEMBANG - Mgs Nazarudin; Jumanah Jumanah (Ta'dib, 2019)
The research objective is to restore drug users through the implementation of Islamic education. The research method used was descriptive qualitative method. The informants considered as the data sources were the drug users, their parents, the owner of the rehabilitation center, Yayasan Pusat Rehabilitasi Narkoba Ar-Rahman Palembang, and the local government. The data were analyzed through descriptive normative analysis. The results of this study are 1) rehabilitation is directed at two aspects namely physical and spiritual recovery; 2) the rehabilitation method used is the method of Dhikr and TC (Therapeutic Community) conducted for 6 months; and 3) Islamic education implemented in rehabilitating drug users with a spiritual moral approach includes teaching education on religious foundations, Shalah together, dhikr, and guidance on reading the Qur’an.